Peran Guru dalam Pengelolaan Kelas di MI Khaerul Huda Bumiayu Kecamatan Bumiayu - Asril Fuadi; Abdul Wachid Bambang Suharto (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2022)
Teachers have a very large contribution to the success of learning in schools. In addition, the teacher also plays a very important role in helping the development of students to achieve their life goals optimally. In the classroom the teacher carries out two main activities, namely teaching and learning activities and class management. Teaching activities are essentially the process of organizing and organizing the environment around students. Classroom management is a series of actions taken by the teacher in an effort to create positive, productive and innovative learning environment conditions so that the teaching and learning process can run according to its objectives. In other words, classroom management is an effort to empower class potential through a set of teacher skills to create a conducive, positive, and productive learning climate and control it if there is a disruption in learning to optimize the learning process so that satisfactory results can be obtained.